The World as Will and Idea (Vol. 3 of 3) - Schopenhauer, Arthur, 1788-1860; Haldane, R. B. Haldane, Viscount (Richard Burdon Haldane), 1856-1928; Kemp, J. (John) (Salt Lake City, UT : Project Gutenberg, 2012)
"The World as Will and Idea (Vol. 3 of 3)" by Arthur Schopenhauer is a philosophical work first published in 1818. Building on Kantian idealism, Schopenhauer argues that the world exists as representation dependent on a perceiving mind, while its inner essence is a blind, unconscious will$1 (Bthe source of all suffering. Through four books, he explores epistemology, ontology, aesthetics, and ethics, proposing that aesthetic experience offers brief escape and only ascetic negation of will brings true redemption. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_World_as_Will_and_Representation
Translation of "Die Welt als Wille und Vorstellung."
Release date is 2012-09-26
Keywords: Philosophy; Knowledge, Theory of; Will; Idea (Philosophy)